2016
DOI: 10.4103/0975-5950.196127
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low-level laser therapy in temporomandibular disorders: A systematic review

Abstract: Purpose:The aim of this systematic review was to assess the efficacy of low-level laser therapy (LLLT) in patients with temporomandibular disorders (TMDs).Methods:Medline search was done from 1997 to 2011 using search terms appropriate to establishing a relation between LLLT and TMD. Only randomized controlled trials were included in this study. Outcome variables related to pain, muscle tenderness, mandibular movements, and Electromyographic (EMG) activity were considered. Of the 242 articles examined, 13 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 14 publications
2
27
0
1
Order By: Relevance
“…The improvement in mandibular movements in the group treated with laser could not be attributed to its recognized analgesic effect as claimed by Núñez et al 32 . The observed improvement in mandibular movements (MIO) in the current study is in accordance with those of other studies [33][34][35] . Variability within individuals might be reflect the effect of psychological factors, such as the desire to feel better which may have influenced physiological processes thereby resulting in the desired outcome.…”
Section: Discussionsupporting
confidence: 93%
“…The improvement in mandibular movements in the group treated with laser could not be attributed to its recognized analgesic effect as claimed by Núñez et al 32 . The observed improvement in mandibular movements (MIO) in the current study is in accordance with those of other studies [33][34][35] . Variability within individuals might be reflect the effect of psychological factors, such as the desire to feel better which may have influenced physiological processes thereby resulting in the desired outcome.…”
Section: Discussionsupporting
confidence: 93%
“…18 Literature reviews usually indicate that LLLT is effective in reducing pain in TMDs mostly through its anti-inflammatory effects. 15,16,19 However, a systematic review in 2012 concluded no definitive results could be drawn on the efficacy of LLLT in the treatment of TMDs except that it was probably more effective in the treatment of TMJ disorders and less effective in masticatory muscle disorders. 20 Therefore, the relative clinical efficacy of LLLT in the treatment of TMD is controversial and sufficient evidence is lacking regarding its benefits in MPDS.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they demonstrated that vascular invasion of bone marrow tissue into the Journal of Dentistry Indonesia 2018, Vol. 25,No. 3,[135][136][137][138][139][140][141] subchondral bone induced the synthesis of matrix metalloproteinases (MMPs) that caused disintegration of the adjacent cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…This is low-level laser (LLL) therapy, which is a conservative and supportive physical therapy that has anti-inflammatory effects and can treat OA of the TMJ (i.e., TMJ-OA). 3 To date, assessment of the anti-inflammatory effects of LLL therapy in clinical studies has only been subjective and based on the induction of pain rather than on the objective evaluation of inflammation. 4 Consequently, there is a need for more objective and controlled studies to determine the effects of LLL therapy on inflammation in TMJ structures.…”
Section: Introductionmentioning
confidence: 99%